Inclusive education: English teachers’ challenges and strategies for hearing-impaired students in Indonesia - Suryanto, Jati; Rachmawati, Berliana Farras; Saefurrohman, Saefurrohman; Sorohiti, Maryam (Universitas Muhammadiyah Sidoarjo, 2025)
English language teaching learning for deaf learners in Indonesia faces linguistic challenges such as limited first-language proficiency, reliance on visual communication, and the phonological complexity of English. This study investigated the challenges faced by teachers, the strategies they adopt, and the perceived effectiveness of their approaches in teaching English to deaf students. Employing a qualitative design, data were collected through in-depth, semi-structured interviews with experienced six English teachers from two urban Sekolah Luar Biasa (SLBs) at the secondary school level. Data were analyzed using thematic analysis, which revealed persistent barriers including students limited linguistic and cognitive skills, inconsistent classroom communication, and inadequate teaching resources. In response, teachers employed visual and multimodal strategies, such as flashcards, realia, Canva-designed materials, educational games, and total communication methods combining sign language, speech, and written text. These approaches enhanced short-term vocabulary acquisition and student engagement yet fell short in fostering long-term language development due to systemic issues such as the absence of adapted curricula and inclusive assessments. The findings highlight that while teacher-led innovations can partially address immediate learning needs, they cannot fully compensate for broader structural gaps. Sustainable improvement in English learning for deaf students requires comprehensive reforms, including the development of adapted curricula, targeted teacher training in inclusive pedagogy, and strengthened institutional support. Such measures are essential to ensure equitable access to English language education and to empower deaf learners with the linguistic skills necessary for academic achievement and social participation in Indonesia’s inclusive education framework.